Anemia in Children under 5 years, The Prevalence and Contributing Factors in Al-Batool Teaching Hospital/Diyala Governorate - SH Al-Zuheiry , Mehdi; Ghazal Noaman, Nadhim; Ammer Abd , Ali (Diyala Journal of Medicine, 2020)
Background: Anemia is a worldwide public health problem, with significant outcomes for health social and economic growth of each country. Anemia is a hemoglobin concentration two standard deviation lower than the mean hemoglobin concentration for a normal population range of the same age and gender. Objective: To assess the prevalence of anemia in children and its contributing factors under 5 years old in Diyala/Iraq. Patients and Methods: A prospective cross sectional study was conducted at Al-Batool maternity and children teaching hospital from the first of August 2017 to first of January 2018. Five hundreds of children from the six months to five years old were included in the current study. Results: The percentage of anemia in the studied sample was 142 (28.4%), from which 104 (73.5%) was iron deficiency anemia, 2 (1.1%) was thalassemia major and intermedia and 6 (4.4%) was B-thalassemia trait and 30 (21%) other type of anemia. There were a highly significant association between anemia and artificial feeding, prolonged breast-feeding, tea consumption, worm infestations, absence of prenatal care, low birth weight, low parental education and low wealth index. They were a significant association between anemia and male gender, rural residency and positive family history of anemia. Conclusion: Anemia still represents a major health problem in children under 5 years in Diyala province with prevalence of 142 (28.4%), most of them 104 (73.5%) was iron deficiency anemia.